Kinetics of Glucose Incorporation by Aphanocapsa 6714 - Pelroy, Richard A. (1973)
Photoautotrophic metabolism of CO(2) was compared with glucose metabolism in the facultative unicellular blue-green alga, Aphanocapsa 6714. Glucose-fed cells incorporated more (14)C into phosphorylated sugar intermediates of the reductive and oxidative pentose phosphate cycles than autotrophic cells. The relative increases were: 140-fold in dark cells; 32-fold in dichlorophenylmethylurea (DCMU)-inhibited cells; and 16-fold in cells assumilating glucose during photosynthetic carbon reduction. On the other hand, incorporation of (14)C from glucose into 3-phosphoglycerate and the amino acid pools of glutamate and aspartate was reduced in dark cells. Rates of protein synthesis in dark and DCMU-inhibited cells were reduced 50 and 80% compared to photoautotrophic cells. In cells assimilating glucose during photosynthesis, rates of (14)C incorporation into the two amino acids and protein were the same as in photoautotrophic cells. Chase experiments, using an excess of (12)C-glucose and CO(2), revealed slow turnover of carbon in dark cells and intermediate turnover rates in DCMU-inhibited cells, when compared to cells assimilating glucose during photosynthesis.